Studi Eksperimental Pengaruh Variasi Mekanis Empat Batang Pada Mesin Pengayak Terhadap Kapasitas Produksi Ayakan - Didi Syamsunarto; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Sifting is a method of grouping granules, which will be separated into one or several groups, thereby separable between the particles passing through the sieve (fine grain) and remaining in the sieve (coarse grain). Specific grain size that can still pass through the sieve, expressed as a boundary grain. In the process of sieving the solid is dropped or thrown onto the sieving surface. Under-sized or undersized particles, or passes (fines), pass through a sieve opening, medium above size or large (oversized), or tails do not pass in sifting. Sifting From the mechanical making of four sticks and the test of the wheat flour with 100 and 200 mesh using DOL250-2 type AC motor, with time of 5 minutes and 229 rpm rotation to sift the flour weighing 500 gr with stem size 75 mm mesh 100 produce the average production was 446.6 gr and the mesh 200 averaged 134.6 grams with the test three times.Keywords : machine, flour, sieving, mesh.